DIGITAL MARKETING TO OPTIMIZE THE ECONOMIC POTENTIAL OF PURISEMANDING VILLAGE - Nanda Agvi , Oktavia; Widy Taurus, Sandy (STIE PGRI Dewantara Jombang, 2024)
Service is important for the STIE PGRI DEWANTARA academic community to understand rural conditions and their relationship to curriculum planning to find out the support and problems that exist in the community. This program will run for approximately one month in February 2023. The expected results include the formation of strong individuals who care when serving the community. The lack of knowledge about digital marketing poses challenges for the development and marketing of Micro, Small and Medium Enterprises (MSMEs) in Purisemanding village. The process includes coordination with village officials, interviews with MSME stakeholders, preparing materials based on the needs of MSMEs in Purisemanding village, and holding digital marketing outreach events. Implementation of the digital marketing outreach program is one type of community development carried out by the group in Purisemanding village. This program aims to increase knowledge about the importance of digital marketing for MSMEs to increase sales and business development. The activity stages include collecting data on MSME information, outreach targets to village officials, the community and MSME stakeholders, as well as implementing programs in collaboration with the community service team.